2011
DOI: 10.3892/ol.2011.441
|View full text |Cite
|
Sign up to set email alerts
|

NY-ESO-1 expression in hepatocellular carcinoma: A potential new marker for early recurrence after surgery

Abstract: Abstract. NY-ESO-1 belongs to the cancer testis antigens (CTA) family, and is identified in a variety of tumors. Certain studies have demonstrated that NY-ESO-1 predicts tumor recurrence and treatment response. No reports are currently available regarding the correlation between NY-ESO-1 and the recurrence of hepatocellular carcinoma (HCC) following surgery. The purpose of the present study was to evaluate the association between NY-ESO-1 and relapse of HCC and to explore the possible mechanisms for this corre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 17 publications
(19 reference statements)
0
22
1
Order By: Relevance
“…8,14,15 Recent reports have shown that NY-ESO-1 expression in hepatocellular carcinoma is associated with disease recurrence following surgical resection, possibly mediated by enhanced migratory ability conferred by NY-ESO-1. 16 Furthermore, the same study and others have implicated NY-ESO-1 as a possible prognostic marker in certain tumor types. 8,16,17 Importantly, the expression of cancer testis antigens by tumors enables the use of targeted immunotherapy, which has shown promise in clinical studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8,14,15 Recent reports have shown that NY-ESO-1 expression in hepatocellular carcinoma is associated with disease recurrence following surgical resection, possibly mediated by enhanced migratory ability conferred by NY-ESO-1. 16 Furthermore, the same study and others have implicated NY-ESO-1 as a possible prognostic marker in certain tumor types. 8,16,17 Importantly, the expression of cancer testis antigens by tumors enables the use of targeted immunotherapy, which has shown promise in clinical studies.…”
Section: Discussionmentioning
confidence: 99%
“…16 Furthermore, the same study and others have implicated NY-ESO-1 as a possible prognostic marker in certain tumor types. 8,16,17 Importantly, the expression of cancer testis antigens by tumors enables the use of targeted immunotherapy, which has shown promise in clinical studies. [18][19][20][21] Variable NY-ESO-1 expression has been described in many malignancies, including melanoma, neuroblastoma, sarcomas, and a variety of carcinomas, such as esophageal, breast, prostate, lung, endometrial, ovarian, uterine, and bladder.…”
Section: Discussionmentioning
confidence: 99%
“…In a subset of tumors, NY-ESO-1 expression has been shown to be lost during remission which is thought to be either a means to evade T-cell-based immunosurveillance or the result of reduced cell proliferation. In hepato cellular carcinoma NY-ESO-1 expression has been associated with metastasis [60,61] and worse outcome following surgery with the possible mechanism of increasing tumor cell migration [62]. In gastrointestinal stromal tumors, the expression of NY-ESO-1 has been associated with tumor progression under imatinib treatment [63].…”
Section: Ny-eso-1 Expression Pattern In Tumorsmentioning
confidence: 99%
“…Interestingly, NY-ESO-1 expression correlates with a reduced recurrence-free survival after tumor resection. A possible explication is the increased migration capacity of NY-ESO-1 expressing cells as it has been described for NY-ESO-1 expressing HepG2 cell lines [32] . Overexpression of SSX has been described for several tumor types; however, the actual percentage of HCC expressing SSX varies between different study cohorts and SSX subtypes.…”
Section: Antitumoral Immune Responsesmentioning
confidence: 99%